The Process of Health Reform in Sierra Leone - World Bank (Washington, DC, 2012)
After years of neglect of its health system, Sierra Leone has had, starting in 1993, remarkable successes in health reform. As there have been few cases of health reform in Africa, a study was undertaken to examine the experience. Through interviews, surveys, focus groups, mass meetings, task forces, workshops and other methods, thousands of Sierra Leoneans have been involved in setting the reform agenda. The health reform effort has been remarkably transparent. By creating their own national health action plan, the Sierra Leoneans were able to establish their own agenda with donors, on their own terms. The department won the Heroes Day Award in 1994 in recognition of improved performance in the Sierra Leonean civil service. This type of public accolade helps to build a positive environment for reform.